SCFمحاسبة الأدوات المالية وفق نظام - دريدش العالية, هزيل عديلة (My University, 2022)
Accounting systems are one of the tools that provide the necessary information to all concerned. In order to develop the quality of this information, Algeria has in recent years committed all its economic institutions to implement a financial accounting system based on international accounting standards and in line with the requirements of the transition to a free economy. This change has affected banks and financial institutions as a fundamental pillar of the economy and their effective role, so the application of the accounting system by banks is important. This study aims to identify the impact of the accounting of financial tools in accordance with the financial accounting system on bank returns. This topic is characterized by complexity and modernization: fair value and financial tools and their relationship to financial performance and performance. This study thus illustrates the relationship between the application of financial tools accounting according to the financial accounting system and the returns of commercial banks in Algeria.
مستغانم BDL دراسة حالة البنك الوطني الجزائري
Keywords: financial accounting system, banking sector, financial tools, financial statements.